A Pragmatic Review of the General Population’s Attitude, Knowledge and Representations with Regard to Continuous Palliative Sedation - Plaisance, Ariane; Tapp, Diane; Rousseau, Evelyne; Bravo, Gina; Masella, Julia (Intervention)

(untitled) (Ordre des travailleurs sociaux et des thérapeutes conjugaux et familiaux du Québec (OTSTCFQ), 2023)
Continuous palliative sedation is an end-of-life practice that consists of inducing a state of unconsciousness in patients who are approaching death to relieve them of severe and refractory symptoms. The Act Respecting End-of-life Care has provided a framework for continuous palliative sedation in the Canadian province of Quebec since 2015. Understanding the general population’s complex attitudes, and knowledge and representations with respect to continuous palliative sedation can contribute to more informed end-of-life care decision-making. Social workers play a crucial role in promoting and implementing enlightened end-of-life choices. The aim of this paper is to explore the general population’s attitude, knowledge and representations with regard to continuous palliative sedation. We used a pragmatic methodology, seeking to explore a real-life knowledge gap while considering resource and time constraints. Two research team members independently selected related studies and extracted their content. We included eight articles involving a total of 18,961 participants. Participants with a positive attitude towards continuous palliative sedation represented 25% to 81% of the study populations. Attitude seems positively affected by the use of euphemisms (i.e. sleep) to describe the intervention. The term “continuous palliative sedation” is unfamiliar to most and is often confused with euthanasia. In the discussion, we offer recommendations for social workers when accompanying patients and families in making end-of-life decisions.